A Critical Review on the Book From Crisis to Collapse: A Mirror in Front of Us - Ahmad Dorosti (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The global financial markets crisis of 2007 and its economic consequences provoked widespread protests and riots in many countries, which in North Africa led to a change of political system. The study and analysis of these events became the basis for the compilation of the book From Crisis to Collapse by Dr. Bashirieh. The present article, which was prepared with the intention of reviewing this book, is organized in three sections: introducing the work, place of the work in the Iranian publishing space and among the other works of the author, and evaluation of form and content of the work. In this book, we are faced with weighty and revised prose and a coherent and uniform text. The theoretical framework of the work is the same theory that the author has formulated for the analysis of revolutions and the process of transition to democracy in his previous works. The organization of the chapters is not done in a clear and distinct way. The title of the work does not reflect the main content of the work completely. Despite the emphasis on the title of the work, the dimensions of sustainability and vulnerability of political systems are less studied inside the text.